Effect of Severe Dietary Magnesium Deficiency on Systemic Bone Density and Removal Torque of Osseointegrated Implants - Landazuri Del Barrio, Ricardo Andres [UNESP]; Giro, Gabriela [UNESP]; Belluci, Marina Montosa [UNESP]; Rodrigues Pereira, Rosa Maria; Marcantonio, Elcio [UNESP]; Massucato, Elaine Maria Sgavioli [UNESP]; Orrico, Silvana Regina Perez [UNESP] (Quintessence Publishing Co Inc, 2010)
Purpose This study evaluated the effect of severe magnesium (Mg) dietary deficiency on systemic bone density and biomechanical resistance of bone tissue to the removal torque of osseointegrated implants Materials and Methods The sample consisted of 45 rats, each received a titanium implant in their tibial metaphysis After 60 days, the animals were divided into three groups (n = 15) according to their dietary Mg the control group received the recommended content of Mg, group Mg1 received a 75% reduction in dietary Mg content, and group Mg2 was fed a diet with a 90% reduction in Mg con tent Animals were sacrificed 150 days after implant placement Serum concentrations of Mg were measured and the effect of Mg deficiency on systemic bone density was evaluated by densitometry of the lumbar vertebrae and femur Biomechanical characteristics were measured by resistance of the bone tissue to removal of the implants Results Lower Mg serum concentrations were found for the Mg1 and Mg2 groups, however, densitometric analysis and torque evaluations showed a statistically significant difference only in the Mg2 group (P < 05) There was a statistically significant difference in removal torque between the Mg2 group and the control group Conclusions This study showed that a severe deficiency of Mg decreased the systemic bone density and removal torque of osseointegrated implants INT J ORAL MAXILLOFAC IMPLANTS 2010 25 1125-1130
Keywords: bone mineral density; dental implants; magnesium deficiency; rats; removal torque